Euthyroid sick syndrome predicts the risk of ischemic stroke-associated pneumonia in the acute stage of ischemic stroke: a nested case-control study - Yu, Shuai; Yan, Jia; Logan, Robert; Tang, Wei-Ting; Ye, Jun-Nan; Feng, Hong-Xuan; Wang, Mei-Xia; Xu, Qin-Rong; Jiang, Xu-Li; Lin, Hai-Yan; Wu, Guan-Hui; Gui, Qian; et al. (Frontiers in Endocrinology, 2024)
Objective Ischemic stroke-associated pneumonia (iSAP) affects about 10% of acute ischemic stroke patients during hospitalization. Current prediction scales for iSAP are insufficient. Identifying early biomarkers for stroke-associated pneumonia is crucial for improving patient outcomes. This study aimed to investigate the predictive value of euthyroid sick syndrome (ESS) for iSAP in acute-stage of ischemic stroke patients. Methods We studied 1767 acute ischemic stroke patients within one week of symptom onset, categorizing them into an infection group (iSAP, n=376) and control group (control, n=1391). COX regression analysis was used to identify the potential risk and protected factors. Kaplan-Meier time-event curves and Log-Rank tests were performed to differentiate infection time in patients with ESS or normal T3 group. Results The iSAP group had higher rates of risk factors like older age, atrial fibrillation, COPD, and ESS, along with elevated levels of WBC, CRP,and FT4 levels (all P < 0.001). Conversely, iSAP patients had lower GCS scores, eGFR, TSH, T3, FT3 (all P < 0.001) and T4 levels (P = 0.005) upon admission. No significant differences were observed in sex, smoking history, hypertension, diabetes, or LDL-C levels (P > 0.05). COX regression analysis identified age, KWST scores, leukocyte count, CRP, and ESS (all P < 0.001) as significantly correlated with iSAP. ROC analysis revealed ESS as a predictor with sensitivity of 35.64% and specificity of 87.92% for SAP prediction, like atrial fibrillation and higher than COPD and eGFR. Conclusion ESS at admission predicts a higher risk of stroke-associated pneumonia in acute-stage of ischemic stroke.